Mahāyāna Buddhism: The Doctrinal Foundations - Irawan, Dedy (Journal of International Buddhist Studies, 2017)
This book offers a general overview of Mahayana Buddhism from historical and doctrinal perspectives. It lays a foundation for Mahayana doctrines in 10 chapters and covers a sufficient range of topicson Indian, Chinese, and Tibetan Buddhism. It also provides a basis for further research on Mahayana Buddhism. Williams starts by introducing the historical background of Mahayana Buddhism. Then, he elaborates upon central themes in Mahayana philosophy, such as Prajñāpāramitā, Mādhyamika, Yogācāra, et cetera. Finally, he elucidates Mahayana soteriological and devotional praxis.